SHR-A1811, a novel anti-HER2 antibody–drug conjugate with optimal drug-to-antibody ratio, efficient tumor killing potency, and favorable safety profiles - Ting Zhang; Jianyan Xu; Junzhao Yin; Yun Gao; Hanwen Zheng; Beibei Fu; Jiakang Sun; Zhibin Xu; Shiwei Tu; Yuchang Mao; Weiyun Wen; Bolei Qu; et al. (PLoS ONE, 2025)
HER2-targeting antibody–drug conjugates (ADCs), especially trastuzumab deruxtecan (T-DXd), have revolutionized the treatment landscape of HER2-expressing or mutant cancers. However, undesired adverse events are still inevitable and it is necessary to discover a HER2-directed ADC with better safety profiles. SHR-A1811 is composed of trastuzumab, a cleavable linker and a novel topoisomerase I inhibitor, SHR169265. The results indicated that SHR169265 shows better permeability, strong cytotoxicity and faster systemic clearance than DXd analog (SHR197971). The drug-to-antibody ratio (DAR) of SHR-A1811 was optimized as 6 via balancing efficacy and toxicity. SHR-A1811 showed HER2-dependent growth inhibition against various cell lines and desirable bystander killing capability. SHR-A1811 led to tumor growth inhibition or even regression in a dose-dependent manner, at least comparable as HRA18-C015 (a synthesized T-DXd) and anti-HER2-SHR169265 (DAR 8) in multiple mouse xenograft models with a range of HER2 expression levels. SHR-A1811 exhibited a good pharmacokinetics profile, outstanding stability in plasma across different species and a favorable preclinical safety profile. The highest non-severely toxic dose (HNSTD) in cynomolgus monkeys was 40 mg/kg with thymus as the main target organ. The above results suggested that SHR-A1811 is a potential best-in-class anti-HER2 ADC with a highly permeable payload, optimized DAR, great potency and better safety profiles. Currently SHR-A1811 has entered phase II and phase III clinical studies for breast cancer, gastric cancer, colorectal cancer, and NSCLC.